Mechanical response analysis of surrounding rock bearing structure of soft rock roadway based on full-length anchorage - Xiangjun WANG; Yingming LI; Guangming ZHAO; Xiangrui MENG; Yi WANG; Xiang CHENG (Meitan kexue jishu, 2023)
A mechanical model of full-length anchoring bolt is established to study the stability of mechanical bearing structure of surrounding rock in high stress soft rock roadway after full-length anchoring bolt. The model considers the dilatancy characteristics of soft rock post-peak strength softening and the stress boundary conditions of full-length bolt, and the analytical formula of bolt stress is derived. Furthermore, the mechanical model of full-length anchored surrounding rock is established by equivalent the anchoring force to the form of volume force. From shallow to deep, it is divided into anchorage residual zone, anchorage plastic softening zone, non-anchorage plastic softening zone and elastic zone, and the stress expression of each zone is deduced. Combined with engineering examples, the influence of space effect, expansion coefficient, bolt length and tray reaction force on surrounding rock stress and bolt stress is analyzed. The results show that under the influence of spatial effect, the deformation and failure of roadway presents progressive development. The concept of ' anchorage control zone ' is proposed, that is, in the process of full-length bolt support, the virtual support force and anchoring force of surrounding rock are in a state of reciprocal growth and decline, thus inhibiting the transfer of surrounding rock stress to the deep and effectively reducing the plastic zone. The earlier the anchor bolt is installed, the greater the deformation of the surrounding rock acting on the rod body, and the easier it is to form a common bearing body with the surrounding rock. The axial force of the anchor bolt is proportional to the expansion coefficient. With the increase of the expansion coefficient, the growth rate of the anchoring force is significantly accelerated, which ensures the recovery effect of the anchor bolt on the radial stress of the surrounding rock. The axial force distribution and peak value of the rod body will increase with the increase of the length of the bolt and the bonding range of the surrounding rock/anchoring agent interface, and then the peak area of the tangential stress of the surrounding rock will shift to the direction of the tunnel wall. The effect of the reaction force of the full-length bolt tray is mainly reflected in improving the stress of the bolt, giving full play to the anchoring effect of the bolt and the ability to protect the surface, and having little effect on the boundary of the residual zone and the plastic zone.